2014
DOI: 10.1590/0104-6632.20140312s00002328
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying properties of maillard conjugates produced from sodium caseinate and locust bean gum

Abstract: -Emulsifying properties of sodium caseinate -locust bean gum Maillard conjugates produced at different temperatures (54 -96 °C), protein/polysaccharide ratios (0.3 -1.0) and reaction times (1 -24 hours) were evaluated. Conjugate formation was confirmed by formation of color and high molecular weight fractions and the decrease of the α s -and β-casein bands. The emulsions stabilized by Maillard conjugates showed good stability. The mean droplet diameter (d 32 ) tended to decrease with the increase of incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…The stability index (the creaming stability) was measured by the height of the serum layer (H S ) with the storage time. The stability index (SI) (Perrechil et al, 2014) was reported as:…”
Section: Sedimentation Stabilitymentioning
confidence: 99%
“…The stability index (the creaming stability) was measured by the height of the serum layer (H S ) with the storage time. The stability index (SI) (Perrechil et al, 2014) was reported as:…”
Section: Sedimentation Stabilitymentioning
confidence: 99%
“…Additionally, due to the anti‐oxidative properties, MRPs can be utilised as encapsulating agents for sensitive core materials in the spray drying process. Last but not least, controlling the processing parameters of the Maillard reaction, such as temperature, incubation time, molar ratio of protein:carbohydrate and pH, are of great importance, as these parameters influenced the degree of glycation of both the dry state and wet state Maillard reaction …”
Section: Resultsmentioning
confidence: 99%
“…Direct monitoring of SCN glycation by gel electrophoresis is complicated by the difficulty to resolve the conjugates mixture. Therefore, glycation of SCN with polysaccharides has been followed indirectly by the disappearance of the casein bands . Differences in the glycation degree of casein fractions were evident from two‐dimentional gel electrophoresis profile where α‐CNs and κ‐CN demonstrated the highest and the lowest susceptibility to glycation respectively.…”
Section: Methods Used To Monitor Glycationmentioning
confidence: 99%
“…60 SCN and locust bean gum (LBG) conjugates formed emulsions of smaller particle size and better emulsion stability than SCN and the unreacted SCN-LBG mixture. 56 Stable lutein-enriched nano-emulsions at pH 3-7 were formed using casein-DX conjugates without any adverse effect on the bioaccessibility of lutein. 64 The double emulsions (water/oil/water, W/O/W) prepared with the use of SCN-DX conjugate 48 and SCN-MD40 and SCN-MD100 conjugates 42 exhibited better acid and heat stability against coalescence and decreased release of B12 during storage compared to emulsions prepared with SCN.…”
Section: Methods Used To Monitor Glycationmentioning
confidence: 99%
See 1 more Smart Citation